1972
DOI: 10.1007/bf00384766
|View full text |Cite
|
Sign up to set email alerts
|

Vacuolar protein in apical and flower-petal cells

Abstract: Vegetative apices, floral apices and flower petals of five Solanaceae (potato, tomato, tobacco, petunia and nightshade) and of corn and Nigella were examined with an electron microscope for the presence of protein bodies in the cell vacuoles. Electron-dense bodies were found in vacuoles of all plants investigated but not in every tissue examined. The bodies observed in the apices are similar to the protein bodies previously found in tomato leaves where they appear to be related to the presence of chymotrypsin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1976
1976
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…These findings suggest that spherical bodies observed in the vacuole are not anthocyanic vacuolar inclusions. Protein bodies, which are spherical, have been observed in vacuoles in some petals including petunia, tomato, tobacco (Shumway et al, 1972), and Rhododendron (Schneider, 1972). However, intravacuolar protein bodies have not been observed in petals in carnation (Smith et al, 1992) and rose (Yamada et al, 2009b).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that spherical bodies observed in the vacuole are not anthocyanic vacuolar inclusions. Protein bodies, which are spherical, have been observed in vacuoles in some petals including petunia, tomato, tobacco (Shumway et al, 1972), and Rhododendron (Schneider, 1972). However, intravacuolar protein bodies have not been observed in petals in carnation (Smith et al, 1992) and rose (Yamada et al, 2009b).…”
Section: Discussionmentioning
confidence: 99%
“…A similar uptake of DIP organelles into vacuoles in root tip cells also seems to be developmentally regulated. It is possible that this process may be related to the formation of what have been termed vacuolar protein bodies in vegetative tissues (Greyson and Mitchell, 1969;Shumway et al, 1972). As little or no DIP labeling was detected in the PSV tonoplast, and little or no labeling for ␦-TIP or ␣-TIP (PSV tonoplast markers) was detected around or in the crystalloid, we hypothesize that the DIP organelles in the cytoplasm are surrounded by a membrane that fuses with the PSV tonoplast to deliver the internal, DIP-containing membranes to the vacuole interior.…”
Section: Discussionmentioning
confidence: 99%
“…Shumway et al (15,16) observed that protein bodies are present in tomato leaves which contain proteinase inhibitor I and later (17) indirectly identified the inhibitor in the protein bodies using immunological methods combined with electron microscope techniques. In this study we have isolated vacuoles from tomato leaves that were induced to accumulate inhibitors I and II and directly confirm that these two proteinase inhibitors are located in vacuoles of the leaf cells.…”
mentioning
confidence: 99%